2018
DOI: 10.1007/s10549-018-4699-9
|View full text |Cite
|
Sign up to set email alerts
|

Differences in breast cancer incidence among young women aged 20–49 years by stage and tumor characteristics, age, race, and ethnicity, 2004–2013

Abstract: Breast cancer among young women is a highly heterogeneous disease. Differences in tumor characteristics by age and race/ethnicity suggest opportunities for further research into personal and cultural factors that may influence breast cancer risk among younger women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
112
0
13

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 161 publications
(133 citation statements)
references
References 45 publications
(51 reference statements)
8
112
0
13
Order By: Relevance
“…It has previously been shown that race/ethnicity influences not only the stage at which a patient presents with breast cancer but also mortality rates . It is well recognized that age is associated with worse outcomes; younger patients are more likely to present at later stages and with worse mortality rates . In addition, BMI has an inverse correlation with health outcomes, education level, and income .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It has previously been shown that race/ethnicity influences not only the stage at which a patient presents with breast cancer but also mortality rates . It is well recognized that age is associated with worse outcomes; younger patients are more likely to present at later stages and with worse mortality rates . In addition, BMI has an inverse correlation with health outcomes, education level, and income .…”
Section: Discussionmentioning
confidence: 99%
“…10 It is well recognized that age is associated with worse outcomes; younger patients are more likely to present at later stages and with worse mortality rates. 11,12 In addition, BMI has an inverse correlation with health outcomes, education level, and income. 21,22 However, there is limited research on the impact of primary language on cancer stages and outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Las tasas estandarizadas por edad estimadas en 2012, muestran que el CaMa tiene una tasa de incidencia de 35,6 casos por 100.000 mujeres-año y una tasa de mortalidad de 10 por 100.000 mujeres-año y el CaCu tiene una incidencia de 18,6 y una mortalidad de 8 por cada 100.000 mujeres respectivamente (3) . Las tasas de mortalidad e incidencia a nivel mundial, también han mostrado diferencias de acuerdo a la etnia; por ejemplo estudios en Estados Unidos han encontrado que las tasas de incidencia por cáncer de cuello uterino son 45% más altas entre las mujeres afrodescendientes y 65% entre las hispanas, en comparación con las mujeres blanco/mestizas (4) ; con relación al cáncer de mama algunos estudios demuestran que las tasas son más altas en mujeres afrodescendientes jóvenes en comparación con mujeres de otras etnias (5) . Por otro lado, la supervivencia, la oportunidad del diagnóstico y acceso a programas de prevención de cáncer entre mujeres afrodescendientes es baja, ya que se han identificado problemas de acceso a servicios de salud, la ausencia de seguro de salud y otros factores sociales y culturales que retrasan la búsqueda de atención (6) .…”
Section: Introductionunclassified